Policy Formulation in Industrial Cities: A Case Study of Environmental Regulation Development in Cilegon City - Hutauruk, Rosinta Paulina; Perdanaputra, Decky; Lestari, Rachma Mutia (Universitas Sang Bumi Ruwa Jurai, 2022)
This study analyzes the formulation process of local environmental policies in Cilegon City, a rapidly industrializing area in Banten Province. Using a qualitative case study, the research focuses on stakeholder interaction, evidence-based decision-making, and institutional coordination in the development of Peraturan Daerah (Regional Regulations) on environmental management. The findings reveal that while formal procedures are followed, challenges remain in inclusive participation, alignment of industrial interests with environmental protection, and the capacity of local government in data utilization. This study offers insights into policy formulation dynamics in urban-industrial regions of Indonesia.